HOMOSEXUAL IN THE DEVELOPMENT OF CONTEMPORARY INDONESIAN LITERATURE - Uman Rejo (Prosiding Seminar Nasional dan Internasional HISKI, 2020)
This paper aims to explore and describe the development of literary works in Indonesia that raise issues on the homosexual’s lifestyle, be it lesbian, gay, bisexual, or transgender groups, which are better known as LGBT people. The focus of his study lies in the development of Indonesian literary works with the theme of homosexuality and several Indonesian academic studies that examine the topic. The method used is descriptive qualitative using a receptive-intertextual approach. The results and discussion show that homosexuality in the development of literature in Indonesia varies greatly in terms of form, conflict, or style of expression. Starting with introducing local culture and wisdom in Indonesia, homosexual rituals, performing arts, Indonesian films from the 70s to the present, the content of Serat Centhini, novels, anthologies of short stories, and literary works published in cyber media (cybernetics). As a product of creative culture, the issues developed in these literary works were followed by the emergence of several Indonesian academic studies that dissect literary works from various perspectives and are explored using contemporary literary theories. Some of these academic studies are in the form of an undergraduate thesis, a master’s thesis and a dissertation, and scientific articles.